Echogenicity changes in the fetal brain, a 6-year follow-up study. (July 2013) - Rosier-van Dunné, F. M. F.; van Wezel-Meijler, G.; de Groot, L.; van Zyl, J. I.; Odendaal, H. J.; de Vries, J. I. P.
Abstract Objective: To asses the relation between echogenicity changes in the fetal brain and neurodevelopmental outcome until 6 years of age. Methods: Fetuses (n = 124) from pregnancies affected by hypertensive disorders (n = 64) or preterm labor (n = 60) at risk for preterm birth (26–34 weeks gestation) were studied. Moderate echogenicity changes (periventricular grade IB, II; intraventricular grade II–III; local basal ganglia/thalami) in the fetal and neonatal brain were related to neurological outcome and Griffiths mental developmental scales quotients at 1, 2 and 6 years. Multiple regression analysis tested the influence of moderate echogenicity changes and perinatal clinical characteristics on composite outcome (death or abnormal neurodevelopment). Results: Moderate echogenicity changes were present in 37/124 (30%) fetuses. Median gestational age and weight at birth were respectively 31 weeks (range 26–43), 1314 g (range 550–4330), mortality was 19%, follow-up loss 10%. Composite outcome was abnormal in 47/124 (38%). Fetal and neonatal moderate intraventricular echodensities were related to cerebral palsy at 6 years (p < 0.04). In the multiple regression analysis only gestational age was related to composite outcome (p = 0.005). Conclusions: Moderate intraventricular echodensities in the fetal brain related to cerebral palsy at 6 years of age. Gestational age at birth was the main predictor of abnormal composite outcome.